Fine Particles Translocation During Infiltration into Porous Media - ASSEED, MOHAMED; RUBER, DALE SWARTZEND (The Libyan Journal of Agriculture, 2023)
Sand-silt mixtures were used as porous medium packed at two bulk densities to investigate whether the fine particles in the mixture tended to be translocated within the porous medium column as a result of the infiltration process. Gamma-ray attenuation technique was used to detect the translocation process through the measurements of bulk density at different positions in the porous medium columns. The bulk density determination were carried out both before and after the infiltration process. Some suggestions of fine particles translocation out of the top 0.5 and 1.0 cm nearest the upper inlet end of the column was found for the lower bulk density (1.8 gm/cm3), but not for the higher (1.9 gm/cm3). The infiltration flow behaviour, however, as analyzed by a derivative form of an approximate theory for infiltration, did not exhibit any non-Darcian behaviour, even for the material of lower bulk density wherein some suggestion of fine-particle translocation had been found.